1984
DOI: 10.1111/j.1751-0813.1984.tb07187.x
|View full text |Cite
|
Sign up to set email alerts
|

Death in sheep following dosing with copper diethylamine oxyquinoline sulphonate as a commercial injectable copper preparation

Abstract: Death occurred in sheep following diethylamine oxyquinoline sulphonate (DOS) copper injections given at recommended dose rates. The copper content in unused portions of DOS copper packs was normal and free of bacterial contamination. Liver and blood copper levels in dead and sick sheep were not high. Sick sheep showed signs of hepatic encephalopathy and dead sheep were generally piled against fences and scrub. Deaths were associated with acute, severe, generalised, centrilobular, hepatocellular necrosis and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Furthermore, acute poisoning is very often associated with oral and parenteral overdoses of Cu salts present in preparations used for the prevention and treatment of Cu deficiency or in anthelmintic drenches [ 5 , 10 , 11 , 45 ]. Soluble formulations, such as Cu edetate and diethylamine oxyquinoline sulphonate (DOS), whose Cu is rapidly available, may be mortal for sheep when administered parenterally, even at recommended doses [ 10 , 46 , 47 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, acute poisoning is very often associated with oral and parenteral overdoses of Cu salts present in preparations used for the prevention and treatment of Cu deficiency or in anthelmintic drenches [ 5 , 10 , 11 , 45 ]. Soluble formulations, such as Cu edetate and diethylamine oxyquinoline sulphonate (DOS), whose Cu is rapidly available, may be mortal for sheep when administered parenterally, even at recommended doses [ 10 , 46 , 47 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, transient lip licking movements, soft faeces, diarrhoea, reduced appetite and tachypnoea have been seen in experimental studies [ 67 ]. In the case described by Mason et al [ 47 ], some sheep showed central nervous signs, such as opisthotonos, head pressing or lack of awareness of surroundings, and dead sheep were found in groups along fences or in the scrub, indicating hepatic encephalopathy in association with liver injury.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A intoxicação ocorreu de forma aguda com a introdução do sal mineral na dieta desses ovinos, os quais já estavam ingerindo excesso de cobre na ração. Essa apresentação é pouco descrita na literatura e foi associada com administração parenteral de cobre, ou ingestão de sulfato de cobre (CuSO 4 ) a 5-10% de pedilúvio (MASON et al, 1984;ORTOLANI et al, 2004;RADOSTITS et al, 2007). Nos casos previamente relatados, são descritas lesões hepáticas severas, semelhantes às observadas neste caso.…”
unclassified